Comparison of post-operative complications following surgical removal of impacted mandibular third molars using rotary instruments and piezosurgery - Mishra, Ravish; Yadav, Deepak; Kandel, Laxmi; Tripathi, Shashank; Shubham, Snigdha (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: This surgical exodontia of mandibular third molar are often associated with a range of postoperative complications like pain, swelling, bleeding, trismus (reduced mouth opening), and in more severe cases, nerve damage and dry socket that can significantly impact a patient’s quality of life. This study was aimed to evaluate and compare the complications associated with surgical removal of impacted mandibular third molar with rotary and piezosurgery devices.Methods: The prospective comparative study was conducted among total 48 patients who required surgical removal of impacted mandibular third molars of varying depth and angulations. Patients were selected and divided alternately into two equal groups of 24 each. Group I underwent surgery with a conventional rotary instrument, while Group II was treated using a piezosurgery unit. Post-operative assessment for complications was done on Days 1, 3, and 7Continuous variables were compared using independent sample t-tests and ANCOVA, whereas, categorical variables were presented as frequencies and percentages and analyzed using Chi-square test. A p-value of less than 0.05 was considered statistically significant.Results: The comparison of pain scores revealed no significant difference between the groups on postoperative Day 1, however, patients treated with piezosurgery experienced significantly less pain on Day 3 and Day 7 compared to the rotary group. Patients in the piezosurgery group consistently showed lower values when swelling was compared and the differences were statistically significant on Days 1 and 3 (p = 0.037 and 0.041 respectively).Conclusions: The surgical removal of impacted mandibular third molars demonstrated that piezosurgery offers several post-operative advantages. Patients treated with piezosurgery experienced significantly less pain, swelling, and trismus compared to those treated with rotary instruments, particularly during the early recovery phase.